Getting “China Ready”. Challenging static and practice based configurations of the Chinese tourist. - Jørgensen, Matias Thuen; Ren, Carina (AEI Insights, 2021)
Lately, the Scandinavian tourism sector has identified the Chinese market as attractive, but difficultly accessible. As a consequence, initiatives have been undertaken in order to make Scandinavia ‘China ready’. In this article, we use an extensive literature review, an example of such an initiative and a range of interviews with practitioners engaged in Chinese-directed tourism in Denmark to demonstrate how the Chinese tourist is configured by different stakeholders in tourism. We discuss how culture is usually deployed in making sense of tourists and show how mostly quantitative methods are used, often in combination with cultural notions of difference, to represent the tourist Other, in this case the Chinese tourist. We show how two opposing configurations of the Chinese tourists emerges. Where one is static and based on cultural difference, the other takes a practice-based perspective, seeing the Chinese tourist as ‘just another customer’. The article points to a third affinity based approach, which enables us to see beyond perceived differences and to focus on meeting grounds where local qualities and characteristics are developed to suit a Chinese market. This abstains from reducing people into stale and stereotypical representations and takes an important step towards getting truly ‘China ready’.